Temporal variation of the geomagnetic conjugacy in Syowa-Iceland pair - Ono, Takayuki (1987)
P(論文) The locations of geomagnetically conjugate points of Syowa and Iceland were examined by using the geomagnetic field models with internal and external magnetic fields. A large secular excursion of the magnetic conjugate point was shown from 1960 to 1990 by tracing the IGRF geomagnetic field lines. The conjugate point of Syowa Station moved from a south-west area to a middlenorth region in Iceland during the last 30 years. The seasonal and daily variations of conjugate points show that the excursion of the conjugate footpoint is minimum around midnight in equinox seasons and it is maximum around summer and winter solstice seasons. departmental bulletin paper